2022
DOI: 10.1101/2022.02.03.22270311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological, endocrine and polygenic predictors of emotional well-being during the COVID-19 pandemic in a longitudinal birth cohort

Abstract: Stress is an established risk factor for somatic and mental disorders. The COVID-19 pandemic and the related countermeasures severely affect the lives of families. Prenatal stress, dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, and genetic factors might impact the well-being of individuals. The present work is part of an ongoing birth cohort study and aims to investigate maternal perceived stress, early childhood HPA axis activity and polygenic risk scores (PRSs) as predictors of emotional we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Mental health such as anxiety and depression, can also affect physical health and reveal physical symptoms. Killgore and colleagues (2020) and Nguyen (found that resilience was found higher in people who tended to exercise, pray regularly and sleep well [31], [32].…”
Section: The Concept Of Resiliencementioning
confidence: 99%
“…Mental health such as anxiety and depression, can also affect physical health and reveal physical symptoms. Killgore and colleagues (2020) and Nguyen (found that resilience was found higher in people who tended to exercise, pray regularly and sleep well [31], [32].…”
Section: The Concept Of Resiliencementioning
confidence: 99%